POSSIBILITY OF DISTRIBUTION THE EXOSOMES DERIVED FROM MULTIPOTENT STROMAL CELLS TO THE MYOCARDIUM AFTER INJECTION INTO THE BONE TISSUE OF A LIMB - Сергей Александрович Кузькин; Игорь Валентинович Майбородин; Александр Андреевич Шевела; Виталина Игоревна Майбородина; Елена Леонидовна Лушникова; Андрей Иванович Шевела (Медицина в Кузбассе)
Objective: The aim of the investigation was to establish the possibility of migration into the heart of EMSCs labeled with a fluorescent dye after their introduction into an artificially created defect in the bone tissue of a limb in an experiment.